Adsorption of turquoise blue QG reactive bye commercial activated carbon in batch reactor: kinetic and equilibrium studies - Schimmel,D. (2010)
The adsorption of reactive turquoise blue QG dye on commercial activated carbon was investigated in a batch reactor to obtain isotherm and kinetic data under different experimental conditions. The adsorbent was characterized by a FTIR method to analyze surface area and pH PZC and to identify functional groups. Experiments were conducted to obtain equilibrium data at 30°C, with the pH effect being assayed in the range of 2 to 8. Experiments were then carried out under the optimal pH condition for dye removal to obtain equilibrium data at 30°C, 45°C and 60°C. Adsorption isotherm models were used to correlate the equilibrium data. Maximum dye removal capacity was observed at a pH of 2 and temperature of 30°C. The kinetic experiments were carried out at a pH of 2 and at three different temperatures: 30°C, 45°C and 60°C. Pseudo-second-order models were used to describe the kinetics of dye adsorption.